Work Commitment as A Mediator of Work Environment Effect on Employee Performance - Hidayati, Elly Wahyu; Supriyanto, Achmad Sani; Ekowati, Vivin Maharani (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study aims to examine the effect of work environment on work commitments, work commitment on employee performance, and work commitment as a mediator of work environment influence on employee performance. The samples are 43 KPPN employees in Malang. Data are collected directly from the respondents through questionnaires and analyzed with path analysis using SPSS software.Â The result shows that work environment has a positive and significant influence on work commitment, and work commitment also has a positive and significant effect on employee performance. Therefore, work commitment proves to be a mediating variable.